Quantitative analysis of chromatin interaction changes upon a 4.3 Mb deletion at mouse 4E2. (December 2015) - Zepeda-Mendoza, Cinthya; Mukhopadhyay, Swagatam; Wong, Emily; Harder, Nathalie; Splinter, Erik; de Wit, Elzo; Eckersley-Maslin, Melanie; Ried, Thomas; Eils, Roland; Rohr, Karl; Mills, Alea; de Laat, Wouter; et al.
Abstract Background Circular chromosome conformation capture (4C) has provided important insights into three dimensional (3D) genome organization and its critical impact on the regulation of gene expression. We developed a new quantitative framework based on polymer physics for the analysis of paired-end sequencing 4C (PE-4Cseq) data. We applied this strategy to the study of chromatin interaction changes upon a 4.3 Mb DNA deletion in mouse region 4E2. Results A significant number of differentially interacting regions (DIRs) and chromatin compaction changes were detected in the deletion chromosome compared to a wild-type (WT) control. Selected DIRs were validated by 3D DNA FISH experiments, demonstrating the robustness of our pipeline. Interestingly, significant overlaps of DIRs with CTCF/Smc1 binding sites and differentially expressed genes were observed. Conclusions Altogether, our PE-4Cseq analysis pipeline provides a comprehensive characterization of DNA deletion effects on chromatin structure and function.